2022
DOI: 10.1007/s11187-021-00583-5
|View full text |Cite
|
Sign up to set email alerts
|

Education, social identity and self-employment over time: evidence from a developing country

Abstract: While the extant literature suggests that an individual’s occupational choice depends on the level of economic development, little is known about how the dynamics of education and social identity impact self-employment choice over time in a developing country setting. The pseudo-panel regression results presented here suggest that higher education decreases the likelihood of individuals’ choice of self-employment over time in India, but increases it in most developed cohorts. Such transitional dynamics are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
3
1
0
Order By: Relevance
“…Conversely, for those with higher education, the effect of IMIS is positive but not statistically significant. This suggests that migrant workers with comparatively lower educational attainment are more inclined to return to their hometowns for entrepreneurship following the implementation of IMIS, consistent with the findings of Tamvada et al (67).…”
Section: Heterogeneity Analysissupporting
confidence: 88%
“…Conversely, for those with higher education, the effect of IMIS is positive but not statistically significant. This suggests that migrant workers with comparatively lower educational attainment are more inclined to return to their hometowns for entrepreneurship following the implementation of IMIS, consistent with the findings of Tamvada et al (67).…”
Section: Heterogeneity Analysissupporting
confidence: 88%
“…Similar results of a positive effect of education on self-employment are reported by (Blanchflower, 2000;Blanchflower and Meyer,1994;Taylor, 1996). However, the results contradict those of (Blanchflower et al, 2001;Livanos, 2009;Tamvada et al, 2022;Van der Sluis et al, 2005), who found that education reduces the likelihood of engaging in self-employment. The results of primary education's effect on self-employment are closely similar to those of (Evans and Leighton, 1989;Johansson, 2000), who reported that education has no significant effect on the probability of self-employment.…”
Section: Determinants Of Self-employment Among the Youth In Ugandasupporting
confidence: 69%
“…This may indicate a negative impact of education on self-employment. In agreement, (Blanchflower et al, 2001;Livanos, 2009;Tamvada et al, 2022) found that education reduces the likelihood of self-employment. Also, Van der Sluis et al (2005) concur that more educated individuals engage in paid employment.…”
Section: Literature Reviewsupporting
confidence: 52%
See 1 more Smart Citation